A novel approach to scaling experimentally produced downburst-like impinging jet outflows. Issue 196 (January 2020) - Romanic, Djordje; Nicolini, Edoardo; Hangan, Horia; Burlando, Massimiliano; Solari, Giovanni
Abstract: Downbursts are intense thunderstorm winds that can be found in most, if not all, regions around the globe. An accurate experimental investigation of downburst winds requires the proper geometric and kinematic scaling between the model downburst ( m ) created in a wind simulator and the full scale downburst event ( p ). This study makes a threefold contribution to further understanding of downburst outflows. First, the article introduces a new scaling methodology for downburst outflows based on the signal decomposition techniques of p and m downburst wind records. Second, the study describes a large set of m downbursts produced in the WindEEE Dome simulator at Western University and critically discusses their similarity with a large set of p events detected in the Mediterranean. Third, using the proposed scaling methodology, this paper attempts to partially reconstruct two p downburst events recorded in Genoa and Livorno, Italy. In total, 17 p and 1400 m downburst outflows are investigated herein, which represents the largest database of p and m downbursts combined. The similarity between p and m downbursts is quantitatively demonstrated for both mean and fluctuating components of the flows. The scaling method is verified by accurately predicting the known anemometer height of p events using m downburst measurements. Graphical abstract: Image 1 Highlights: Novel methodology for downburst scaling in wind simulators developed. 1400 and 17 physically simulated and full scale events, respectively, analyzed. Transient and turbulent features of physically simulated downbursts investigated. Two downbursts in the Mediterranean reconstructed from simulations in WindEEE Dome.